A Lys49 Phospholipase A2, Isolated from Bothrops asper Snake Venom, Induces Lipid Droplet Formation in Macrophages Which Depends on Distinct Signaling Pathways and the C-Terminal Region. (24th December 2012) - Cristina Giannotti, Karina; Leiguez, Elbio; Moreira, Vanessa; Nascimento, Neide Galvão; Lomonte, Bruno; Gutiérrez, José Maria; Lopes de Melo, Robson; Teixeira, Catarina
Abstract : MT-II, a Lys49PLA2 homologue devoid of catalytic activity from B. asper venom, stimulates inflammatory events in macrophages. We investigated the ability of MT-II to induce formation of lipid droplets (LDs), key elements of inflammatory responses, in isolated macrophages and participation of protein kinases and intracellular PLA2 s in this effect. Influence of MT-II on PLIN2 recruitment and expression was assessed, and the effects of some synthetic peptides on LD formation were further evaluated. At noncytotoxic concentrations, MT-II directly activated macrophages to form LDs. This effect was reproduced by a synthetic peptide corresponding to the C-terminal sequence 115–129 of MT-II, evidencing the critical role of C-terminus for MT-II-induced effect. Moreover, MT-II induced expression and recruitment of PLIN2. Pharmacological interventions with specific inhibitors showed that PKC, PI3K, ERK1/2, and iPLA2, but not P38 MAPK or cPLA2, signaling pathways are involved in LD formation induced by MT-II. This sPLA2 homologue also induced synthesis of PGE2 that colocalized to LDs. In conclusion, MT-II is able to induce formation of LDs committed to PGE2 formation in a process dependent on C-terminal loop engagement and regulated by distinct protein kinases and iPLA2 . LDs may constitute an important inflammatory mechanism triggered by MT-II in macrophages.